The Influence of the Empowerment of Group Farmers Through Local Potential on the Welfare Community at Desa Tanjung Beringin 1 Kecamatan Sumbul - Suseno, Bambang; Evelina Br. Gurning (Jurnal Ekonomi, 2024)
Influence of the Empowerment of Group Farmers Through Local Potential on the Welfare Community at Desa Tanjung Beringin 1 Kecamatan Sumbul.